2009
DOI: 10.1037/a0014732
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric diagnoses as contemporaneous risk factors for suicide attempts among adolescents and young adults: Developmental changes.

Abstract: The purpose of this prospective, naturalistic study was to examine the relationships between suicide attempts and contemporaneous psychiatric disorders, and developmental changes in these relationships from adolescence to young adulthood. The sample consisted of 180 adolescents, 12-19 years of age at hospitalization, repeatedly assessed for up to 13 years (n = 1,825 assessments). Semistructured psychiatric diagnostic instruments were administered at repeated assessments to assess psychiatric disorders and suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
154
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(169 citation statements)
references
References 45 publications
13
154
0
2
Order By: Relevance
“…Moreover, researches have shown an association with ADHD and internet dependency and suicide attempts (27,28). Suicide attempts and internet dependency are considered impulsive behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, researches have shown an association with ADHD and internet dependency and suicide attempts (27,28). Suicide attempts and internet dependency are considered impulsive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies evaluating the text anxiety, we have not come across with a research directly gravitated towards ADHD. ADHD has negative effects on the success of education (27)(28)(29)(30). Several features of ADHD contribute to poor performance in test situations; inherent difficulties with impulse control, attention capacity, and hyperactivity disrupt the acquisition of basic academic skills (31).…”
Section: Discussionmentioning
confidence: 99%
“…Relationships between these factors and suicidal behaviour have been shown in indigenous youth and in other adolescent samples (e.g., Borowsky et al, 1999;Chino & Fullerton-Gleason, 2006;Goldston et al, 2009;Howard-Pitney et al, 1992;Freedenthal & Stiffman, 2004;Peter, Roberts, Buzdugan, 2008;Schilling, Aseltine, Glanovsky, James, & Jacobs, 2009). Furthermore, mood and substance use disorders have been found to be prevalent in different samples of youth who completed suicide (e.g., Portzky, Audenaert, & van Heeringen, 2005;Marttunen, Aro, Henriksson, & Lönnqvist, 1991;Sigurdson et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…In 2009, 13.8% of United States of America (USA) high school students reported that they had seriously considered attempting suicide during the 12 months preceding the survey. In the study, 6.3% of students reported that they had actually attempted suicide one or more times during the same period. [8] Arria and colleagues examined suicidal ideation among college students.…”
Section: Suicidality In Children and Adolescents Suicidal Ideation Anmentioning
confidence: 99%
“…Most children with suicidal behavior have at least one psychiatric disorder with mood disorders being the most common. [4][5][6][7] As such, the goal of this paper is to review the literature on suicidality in children and adolescents.…”
mentioning
confidence: 99%